Effect of The Work Environment on Employee Performance PT. Lion Super Indo Grage City Mall Cirebon - Tedi Kustandi; Linda Norhan; Nurrohmah (Jurnal Mantik, 2021)
The purpose and objective of taking the title is to find out how much influence the work environment has on employee performance. The types of data used in this study are primary data and secondary data. Collecting data using a questionnaire, with a sampling technique method, taking a sample of 36 employees. Other data obtained from observations, interviews, and literature study. This study analyzes two variables in which the dependent variable is the employee performance and the independent variable is the work environment. The data analysis method used is simple linear regression analysis, correlation coefficient, and determination with the help of SPSS version 20 for windows. Based on the results of data analysis, the regression equation obtained is as follows: Y = 13,124 + 0,335X The results of the t test, the work environment has a positive and significant effect on employee performance with a tcount of 4.425> a t-table value of 1.691. Work environment on employee performance at PT. Lion Super Indo has a strong relationship, it is proven that the correlation number is 0.604, because the magnitude> 0.50 is said to be strong, and the coefficient of determination (R²) is 0.365. This shows that the influence of the work environment on employee performance is strong and influential, namely 36.5% and the remaining 63.5% is determined by other factors that are not present in this study.